Data from: Is ungulate migration culturally transmitted? Evidence of social learning from translocated animals - Jesmer, Brett R.; Merkle, Jerod A.; Goheen, Jacob R.; Aikens, Ellen O.; Beck, Jeffrey L.; Courtemanch, Alyson B.; Hurley, Mark A.; McWhirter, Douglas E.; Miyasaki, Hollie M.; Monteith, Kevin L.; Kauffman, Matthew J. (Zenodo, 2019)
Ungulate migrations are assumed to stem from learning and cultural transmission of information regarding seasonal distribution of forage, but this hypothesis has not been tested empirically. We compared the migratory propensities of bighorn sheep and moose translocated into novel habitats with those of historical populations that had persisted for hundreds of years. Whereas individuals from historical populations were largely migratory, translocated individuals initially were not. After multiple decades, however, translocated populations gained knowledge about surfing green waves of forage (tracking plant phenology) and increased their propensity to migrate. Our findings indicate that learning and cultural transmission are the primary mechanisms by which ungulate migrations evolve. Loss of migration will therefore expunge generations of knowledge about the locations of high-quality forage and likely suppress population abundance. Ungulate migration a cultural phenomenon Data describes the migratory propensity of GPS-collared bighorn sheep (n=267) and moose (n=189) and their ability track plant phenology. Each line in the data frame describes where an individual (AID) resided (POP; see Fig. 1 of manuscript for map illustrating spatial distribution of individuals), the year in which the animals movements were observed (YEAR), whether the animal was migratory or not (MIG), and how well the animal tracked plant phenology (OBSmedIRG). The amount of knowledge an individual possessed about its landscape (KNOW) is a function of how well it tracked plant phenology (OBSmedIRG) relative to simulated individuals that foraged at random (RANDmedIRG) and simulated individuals with complete knowledge about local patterns of plant phenology (OMNmedIRG). These measurements were collected for individual bighorn sheep and moose within populations that were translocated into their respective landscapes zero to greater than two hundred years ago (TIME). Mig_Culture_Ungulate.csv